Soil, nutrient, and fertiliser requirements for maize (Zea mays) production: A narrative review - Kuunya, Ronald; Mustafa Ahmed Osman, Magdoline; Ragán, Péter (Acta Agraria Debreceniensis, 2025)
Maize (Zea mays) is a key staple crop essential for global food security, with its productivity heavily influenced by soil, nutrient, and fertiliser management. This review examines the requirements for optimal maize production by analysing recent literature on soil properties, nutrient uptake, and fertilisation practices. A systematic approach was used to gather relevant studies from Google Scholar, Scopus, and Web of Science, focusing on peer-reviewed articles, books, and conference proceedings published in the last 10 years. Keywords such as “maize soil requirements” and “nutrient management for maize” guided the search, and both global and region-specific research were included to capture diverse agricultural systems and environments. Key insights were extracted to understand best practices, challenges, and technological advancements influencing maize yield. The findings provide a comprehensive overview of the current state of knowledge on soil and nutrient management for maize cultivation, highlighting optimal practices and emerging trends in fertilisation techniques. The review aims to support improved management strategies for yield maximisation and sustainable maize production across various agricultural landscapes, ensuring food security in the face of changing environmental conditions.